2005
DOI: 10.1177/1525822x04271029
|View full text |Cite
|
Sign up to set email alerts
|

Thinking Aloud to Create Better Condom Use Questions

Abstract: Measuring the effects of HIV/AIDS prevention efforts through self-reported condom use data is problematic since such data are frequently subject to bias. The purpose of this study was to pretest a sexual behavior instrument to identify ways to improve comprehension and decrease recall and social desirability bias. The method used was cognitive interviewing, in which fifteen sex workers were asked to “think aloud” as they problem solved simulated tasks. Results indicated that (1) a lexicon of culturally appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…44 They were not distinctly different from what is known about recall in other survey populations. 45 While recommendations for questionnaire construction to enhance recall of past events may be no different in this population, the process provided valuable information about recall for specific information and the maximum measurement periods for which valid responses could be expected.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…44 They were not distinctly different from what is known about recall in other survey populations. 45 While recommendations for questionnaire construction to enhance recall of past events may be no different in this population, the process provided valuable information about recall for specific information and the maximum measurement periods for which valid responses could be expected.…”
Section: Discussionmentioning
confidence: 80%
“…Edwards et al also found the "think aloud" technique to be challenging in a street-involved population. 44 For homeless individuals with mental health issues and who also often have cognitive impairment, it is not surprising that the metacognitive skills required for the "think aloud" approach were quite challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The subject of these measures are widely invoked in social marketing efforts to curb HIV transmission, and we believe highly sensitive and prone to social desirability (Edwards, Thomsen and Toroitich-Ruto 2005): Lifetime sexual partners: What is the total number of sexual partners you have had in your life?Condom use: Did you use a condom the last time you had sex with this partner?Discussing HIV: At the time you first had sex with this partner, had you ever discussed HIV with him/her?HIV testing: Have you ever been tested for HIV? We modeled lifetime sexual partners using negative binomial regression; and condom use, discussing HIV, and HIV testing using logistic regression (with correlation among partners of the same respondent, when applicable). Our approach was to first model the outcome using respondent covariates we expected would influence the outcome but were not the focus of our research question about fieldworker effects.…”
Section: Methodsmentioning
confidence: 99%
“…The 7 day time period was chosen because of previous work with this population, which indicated that sex workers could comfortably count clients back this far, but not farther. 11 Secondary outcomes of interest were the number and proportion of protected sexual acts with different partner types.…”
Section: Condom Usementioning
confidence: 99%